Dissimilaridade, parâmetros genéticos, índices de seleção e resistência a Meloidogyne spp. em alface biofortificada - Sousa, Luciana Alves de (2020)
Lettuce is the most prominent vegetable within the group of leafy vegetables, presenting the highest consumption and economic importance in the world. Obtaining biofortified foods is a constant objective in breeding programs in addition to cultivars resistant to phytopathogens, such as gall nematodes. The knowledge of dissimilarity, of estimates of genetic parameters, such as heritability, the coefficient of genetic and environmental variation, the correlations between the characteristics of interest, allow obtaining relevant knowledge about the evaluated germplasm. The application of selection indexes allows the simultaneous analysis of several characters of interest, enabling the identification of selection gains and the choice of promising genotypes. The objective of this study was to verify the genetic dissimilarity, the genetic parameters, the correlations, the efficiency of selection indexes and the resistance to Meloidogyne spp. in biofortified lettuce. Three experiments were carried out, one with 91 genotypes of lettuce (86 genotypes from hybridization between the cultivars Pira 72 versus Uberlândia 10000 (rich in carotenoids), followed by three successive self-fertilizations, and 5 commercial cultivars (Grand Rapids; UFU MC BIOFORT1; Pira 72; Uberlândia 10000 and Robusta). Nematode resistance was evaluated in 49 genotypes (43 belonging to the F6 generation of the same breeding program + 6 commercial cultivars (Pira 72, Uberlândia 10000, Robusta, Grand Rapids Albina 1, Grand Rapids Albina 2 and Grand Rapids Albina 3). The third experiment was carried out in 30 lettuce genotypes (29 strains of curly lettuce of the purple type, from the same breeding program, followed by seven successive self-fertilizations and the commercial cultivar Pira 72). There is genetic divergence between the biofortified lettuce germplasm and it was possible to know the associations between the characters of interest,( such as pigments,) through correlations network. The selection indexes of Smith and Hazel, Willian’s and Mulamba and Mock made good gains of selection for the characteristics evaluated in germplasm of biofortified lettuce, with the Mulamba and Mock index standing out in the choice of superior genotypes of red lettuce. Superior genotypes with good productive potential were selected, combined with good nutritional characteristics, resistant to Meloidogyne spp., being promising to be used in future breeding programs and to be launched as new cultivars of biofortified lettuce.